Epidemiology of parasitism and poly-parasitism involving intestinal helminths among school children from different residential settings in Nandi County, Kenya - Jimmy Ruto; Chrispinus Siteti Mulambalah (Wolters Kluwer Medknow Publications, 2016)
Background: Intestinal helminthiases present a major public health problem worldwide. In Africa, the prevalence varies in countries and within regions. The study aimed at assessing the prevalence of parasitism and poly-parasitism due to intestinal helminths in rural and urban settings. Settings and Design: A 6-month cross-sectional school-based study was undertaken in Nandi County, Kenya, to determine the prevalence of intestinal helminthiases in school children. Materials and Methods: A total of 2967 fecal samples were collected and analyzed to detect the presence of helminth ova, larvae, segments, or adults. Modified formal-ether concentration technique was used. Results: The study findings revealed that three helminth species were prevalent and were associated with intestinal helminthiases with an overall prevalence of ascariasis 55.8%, trichuriasis 26.9%, and hookworm disease 24.8%. There was no significant difference in the prevalence of intestinal helminth single infestations among the study sites and between sexes (P > 0.05). The prevalence of multiple infestations was established as 34.7% and was common in estates and villages (40-50%) than in towns (18%). Poly-parasitism involving 2-3 helminths was prevalent in 8.4-25.4% than those with 4-5 species of 0.07-0.7%. A statistically significant difference among the different types of poly-helminthic infestations was established (P < 0.05). However, no significant difference was established in the prevalence of poly-helminthism in the study sites (P > 0.05). Conclusion: The study confirmed that single and multiple helminth intestinal infestations were prevalent in rural and urban areas. Residential area was found not to be associated with multiple parasitism. The findings support the view that intestinal helminthiases require intervention. Recommendation: Strategic intervention in the form of mass diagnosis and treatment by the use of effective broad spectrum anthelmintic(s) and public health education are recommended.